2012
DOI: 10.1540/jsmr.48.47
|View full text |Cite
|
Sign up to set email alerts
|

Local differences in electrogastrographic responses to the stress of the mirror drawing test (MDT) as determined by multichannel electrogastrography

Abstract: Electrogastrograms (EGGs) were recorded in human subjects (n=58) at 16 locations on the thoraco-abdominal surface before (at rest) and during the stress of the mirror drawing test (MDT) and after having a test meal. The power amplitude ratios and power content ratios of MDT to rest (MDT/rest) and postprandial state to rest (PPR/rest) were compared between gastric channels 5 and 8, and the infraumbilical channels 12, 13, 14, 15, and 16. Generally, the ratio of the 3-cpm group in channels 5 and 8 was lower than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…We have previously reported the effects of the acute stress of MDT on the gastric and colonic facilitation or inhibition with EGG. However, MDT stress did not appear to exert effects on the intestinal EGG activity (6, 8, 12). …”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…We have previously reported the effects of the acute stress of MDT on the gastric and colonic facilitation or inhibition with EGG. However, MDT stress did not appear to exert effects on the intestinal EGG activity (6, 8, 12). …”
Section: Discussionmentioning
confidence: 81%
“…However, the finding of a significantly higher power ratio of the MDTr –1 of the infraumbilical 3 cpm than that in the epigastric recording during MDT suggested that the MDT stress inhibited gastric EGG and facilitated colonic EGG. In addition, topographic EGG maps drawn according to the power content ratio of the MDTr –1 and the absolute power ratio of MDTr –1 supported this idea (6). Similar findings of colonic facilitation have been reported with manometry (13, 25, 26, 27, 28, 29).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations